Equal Access or Empowerment? Understanding Youth Participation in Cultural Institutions through Two Swedish Case Studies - Lindström Sol, Sofia (Conjunctions. Transdisciplinary Journal of Cultural Participation, 2024)
The concept of cultural participation is seldom defined in policy but carries a positive connotation. The aim of this article is to understand how participation is made meaningful by policy stakeholders, exemplified by a Swedish municipality, with special attention directed towards two cultural institutions working to enhance young people’s participation. The analysis considered levels of interest in participation, from the policy level, managerial level and civil servant level. The analysis found the meaning of participation shifted from a focus on equal access to empowering young people as a marginalised group, mirroring theories of a shift from a cultural democratisation paradigm to a cultural democracy paradigm in cultural policy. The civil servants shared an understanding that it is possible to distribute power from adults to young people, but the overlap of the two paradigms in the goal of achieving participation resulted in tensions and paradoxes regarding the issue of negotiating power.